The Behaviour Shields against Terrorism - Zora Arfina Sukabdi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Limited empirical research into terrorist offenders’ rehabilitation invites researchers to conduct further researches in the area. Rehabilitating terrorist offenders is a challenging issue, particularly in determining if the offender is genuinely deradicalised, hence observing their verbal and non-verbal attitudes and actions can be an option, and if there is an adequate method in measuring behaviour changes. This study aims to systematically identify behaviour protections against terrorism for the purpose in the prevention of re-offending. Focus Group Discussion with Indonesian counterterrorism experts and professionals were conducted in data collection with qualitative method of analysis. The study shows there are eighteen protective behaviour indicators against terrorism when assessing offenders and their risks. The findings may assist practitioners in designing terrorism prevention and rehabilitation.